Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/ijerph19042106
|View full text |Cite
|
Sign up to set email alerts
|

Good Care during COVID-19: A Narrative Approach to Care Home Staff’s Experiences of the Pandemic

Abstract: Due to its major impact on Dutch care homes for older people, the COVID-19 pandemic has presented care staff with unprecedented challenges. Studies investigating the experiences of care staff during the COVID-19 pandemic have shown its negative impact on their wellbeing. We aimed to supplement this knowledge by taking a narrative approach. We drew upon 424 personal narratives written by care staff during their work in a Dutch care home during the COVID-19 pandemic. Firstly, our results show that care staff hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…Carrying the load refers to the cognitive, socio-emotional, and psychological burden carried by HCWs throughout the pandemic and the impact on their health and wellbeing. This burden, or “emotional load” (Dohmen et al, 2022), was directly linked to work-related demands and tremendous responsibilities placed on HCWs in the LTC sector. Twenty-five of the 40 studies reported negative emotions and internal struggles that diverse groups of LTC workers (i.e., care aides, nurses, physicians) experienced in caring for infected and dying residents.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Carrying the load refers to the cognitive, socio-emotional, and psychological burden carried by HCWs throughout the pandemic and the impact on their health and wellbeing. This burden, or “emotional load” (Dohmen et al, 2022), was directly linked to work-related demands and tremendous responsibilities placed on HCWs in the LTC sector. Twenty-five of the 40 studies reported negative emotions and internal struggles that diverse groups of LTC workers (i.e., care aides, nurses, physicians) experienced in caring for infected and dying residents.…”
Section: Resultsmentioning
confidence: 99%
“…The effects of carrying this emotional burden and feelings of guilt often led to “internal conflict” and “moral distress” for HCWs (Dohmen et al, 2022). Most HCWs conveyed a deep-seated grief, anxiety, and concern for the quality of life of residents as many deteriorated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Carrying the load refers to the cognitive, socio-emotional, and psychological burden carried by HCWs throughout the pandemic and impact on their health and wellbeing. This burden, or "emotional load" (Dohmen et al, 2022), was directly linked to work-related demands and tremendous responsibilities placed on HCWs in the LTC sector. Twenty-five of the 40 studies reported negative emotions and internal struggles that LTC workers experienced in caring for infected and dying residents.…”
Section: Carrying the Loadmentioning
confidence: 99%
“…The effects of carrying this emotional burden and feelings of guilt often led to "internal conflict" and "moral distress" for HCWs (Dohmen et al, 2022;Scerri et al, 2022). One participant expressed that "[h]er emotional turmoil was associated with moral distress of not being able 'to be a nurse' in the current circumstances" (Scerri et al, 2022, p.6) as a result of COVID-19 mitigation measures.…”
Section: Carrying the Loadmentioning
confidence: 99%